2018
DOI: 10.1021/acs.chemmater.8b03627
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Mechanochemical Modulation of Carbon Nanotube Forest Growth

Abstract: Ordered synthesis of one-dimensional nanostructures, such as carbon nanotubes (CNTs), involves competition between the growth kinetics of individual structures, their physical entanglement, and intermolecular forces that cause coupling of structures in close proximity. Specifically, CNT synthesis by chemical vapor deposition can directly produce films and fibers by providing CNT growth sites in close proximity such that the CNTs self-align into macroscopic assemblies. Because CNTs are mechanically coupled duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To support this trend, E has previously been observed to scale with NF diameter, 79 the number of CNT walls and contact area, 40,114 carbon deposition on the array, 45 and CNT V f . 42,45,114,115…”
Section: Mechanistic Insights For Cnt-substrate Adhesionmentioning
confidence: 99%
“…To support this trend, E has previously been observed to scale with NF diameter, 79 the number of CNT walls and contact area, 40,114 carbon deposition on the array, 45 and CNT V f . 42,45,114,115…”
Section: Mechanistic Insights For Cnt-substrate Adhesionmentioning
confidence: 99%
“…pointed out that a mechanical coupling between growing CNTs transmits forces that can create an energy barrier that ultimately exceeds energy available from chemical reaction at underlying catalyst particles [122], stunting CNT growth. Another recent report showed that CNT forests growing under a compressive mechanical decreased the observed CNT population growth rate [107]. These studies suggest that mechanical stress acting on catalyst nanoparticles alter the activation energy of CNT growth.…”
Section: Force-modulated Growth Ratesmentioning
confidence: 82%
“…These studies suggest that mechanical stress acting on catalyst nanoparticles alter the activation energy of CNT growth. In these studies, the collective CNT forest grew at a decreased rate with Arrhenius-like dependence [107]:…”
Section: Force-modulated Growth Ratesmentioning
confidence: 99%
See 2 more Smart Citations